Udział Kościoła katolickiego we wprowadzaniu pokoju pomiędzy plemionami prowincji Southern Highlands w diecezji Mendi w Papui-Nowej Gwinei - Król, Marek (Annales Missiologici Posnanienses, 2014)
The author describes several social and peace-making initiatives which were undertaken in the last decades by the Catholic organizations active within the diocese of Mendi in Papua New Guinea. The country gained independence in 1975, but remained culturally diversified. The basic identity for most of the citizens is still related to the tribal level. Political conflicts, corruption, abuse of alcohol and narcotics resulted in the past decades in several outbursts of violence among tribes of the Southern Highlands Province. Since the central government was unable to answer this challenge, the Catholic organizations of the Mendi diocese became very much involved in the peace-making process and other social initiatives. Activities of two Catholic organizations are described in more detail, namely the Diocesan Development Secretariat and the Justice and Peace Group, which have succeeded in mediations among several tribes.